Impact of Sex and Contact‐to‐Device Time on Clinical Outcomes in Acute ST‐Segment Elevation Myocardial Infarction—Findings From the National Cardiovascular Data Registry. Issue 1 (11th January 2017) - Roswell, Robert O.; Kunkes, Jordan; Chen, Anita Y.; Chiswell, Karen; Iqbal, Sohah; Roe, Matthew T.; Bangalore, Sripal
Abstract : Background: Emergent myocardial reperfusion via primary percutaneous coronary intervention is optimal care for patients presenting with ST‐segment elevation myocardial infarction (STEMI). Delays in such interventions are associated with increases in mortality. With the shift in focus to contact‐to‐device (C2D) time as a new perfusion metric, this study was designed to examine how sex affects C2D time and mortality in STEMI patients. Methods and Results: Clinical data on male and female STEMI patients were extracted and analyzed from the National Cardiovascular Data Registry from July 1, 2008 to December 31, 2014. A total of 102 515 patients were included in the final analytic cohort. The median C2D time in female patients with STEMI was delayed when compared to male patients (80 [65–97] versus 75 [61–90] minutes; P <0.001). The unadjusted mortality was higher in female patients when compared to male patients with STEMI (4.1% versus 2.0%; P <0.001). For every 5‐minute increase in C2D time, the adjusted odds ratio for mortality was 1.04 (95% CI, 1.03–1.06) for female patients with STEMI and 1.07 (95% CI, 1.06–1.09) for male patients ( P for sex by C2D interaction=0.003). Conclusions: To date, this is the largest analysis of STEMI patients that measures the impact of the new recommended C2D reperfusion metric on in‐hospital mortality. Female STEMI patients have longer C2D times and increased mortality. The disparity can be improved and survival can increase in this high‐risk patient cohort by decreasing systems issues that cause increased reperfusion times in female STEMI patients.